Cloud Analytics and its Implementation Challenges - Kalpana, G; Chaitanya, NV (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is “a style of computing in which scalable and elastic IT-enabled capabilities are delivered as a service to external customers using Internet technologies.”. Cloud computing is capable of enhancing business productivity and agility while allowing for greater efficiency and reducing costs. It is also possible to migrate big data to cloud. Increasingly, the focus of organizations has been on the ways that cloud will power data analytics. Cloud analytics enable organizations to move business intelligence, data warehouse operations and Online Analytical Processing (OLAP) to cloud. Data management, security, integration, compliance issues, poor software architecture and design are some of the issues that motivates with cloud inclusion for analytics solution. This paper aims in outlining the data analytics, cloud computing, cloud Analytics, and its Architecture, applications of cloud analytics and implementation challenges along with suggested solutions.